PEMETAAN LORONG GUA GARUNGGANG UNTUK GEOWISATA DI DESA KARANG TENGAH, KECAMATAN BABAKAN MADANG, KABUPATEN BOGOR, JAWA BARAT - SARI, GRANDIS KUMALA; MUZANI, Dr; suhardjo, Drs (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2018)
The purpose of this research is to map passage of Garunggang cave so that can be made a recommendation for geotourism activity. This research used the descriptive method. The population of this research are all survey station in each cave system which amount 93 stastion covering 26 station in first cave system and 67 station in second cave system. This research held on 2 – 4 September 2016. The research results show that there are two cave system is formed in the Garunggang Cave. Both of them including type of watery cave and the majority is the cave horizontal. First cave system have a distance about 95,12 meters with one entrance that’s a Entrance 1 and four aven (a hole on the top of passage cave). First cave system divided into four subsystem with classification for subsystem 1 and subsystem 2 including semi – limited access and subsystem 3 and subsystem 4 including limited access. Subsystem 2 is the subsystem with most various ornament but subsystem 3 have not ornament. Second cave system have a distance about 353,65 meters. Second cave system have three entrance and one aven. Entrance 3 use for general tourist and Entrance 2 with Entrance 4 for special tourist. Second cave system divided into seven subsystem with subsystem 1 including limited access and for subsystem 2 until subsystem 7 including semi – limites access. Although subsystem 1 including limited access, but have most various ornament. Followed by subsystem 2, subsystem 5, subsystem 3, and subsystem 7. Subsystem 6 only have one type of ornament and subsystem 4 have not ornament.Based on the above condition, it can be made a recommendation cave tour track for general tourist, special tourist, and educational tourist. Keyword: Maping of cave, cave geotourism, ornament of cave